Merajut Asa Implementasi Food Preference di Rumah Sakit Swasta - Ni Luh Ayu Kalimantari; Ida Bagus Teddy Prianthara (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe purpose of this study was to find out to find out how the implementation of the food preference in organizing food at Surya Husadha Nusa Dua Badung Hospital and the obstacles that occur in the implementation of a food preference. This research was conducted at Surya Husadha Nusa Dua Hospital, Badung Regency. The design of this study is qualitative, namely to understand the phenomenon of food preference implementation preference in organizing food. Technically, data collection uses interviews with informants. The research informants consisted of elements involved in the mechanism of organizing food at Surya Husadha Nusa Dua and patient. The results of the study showed that the food preference imple- mentation in Surya Husadha Nusa Dua Hospital had 1) effective communication in food preference implementation, 2) inadequate resources in the implementation of food preferences, 3) the attitude of the implementers in the food preference implementation was already underway well and 4) the bureaucratic structure in the implementation of a food preference knows the duties and responsibilities. The organizational structure has gone well. Then the obstacles in the implementation of food preferences include: The semi out-sourcing system that is used in hospitals triggers delays in food distribution and ineffective communication between task implementers, and the lack of human resources causes implementers to be more oriented towards the target time of completion of work rather than on the results or quality of work.